THE DESCRIPTIVE ANALYSIS OF STUDENTS' ABILITY IN WRITING DESCRIPTIVE TEXT BY USING PICTURE AT THE EIGHTH GRADE OF SMP SWASTA MASYARAKAT DAMAI IN 2020/2021 - Yasminar Amaerita Telaumbanua; Elwin Piarawan Zebua (Universitas Nias, 2022)
Writing is one of English skills that must be learned by the students. The syllabus of 2013 Curiculum of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan expects the students to be able to write the descriptive text in accordance with the context of its use. In fact, most of the students were not able to write the descriptive text and fulfill the requirements needed for writing descriptive text. Therefore, the purpose of the research was describing the students‟ ability in writing descriptive text by using picture as media and the picture contribution to students in writing desciptive text. The method used in the research was descriptive qualitative. The data were collected through students worksheets and interview both students and English teacher. Furthermore, the informant of the research was class VIII-B students of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan which consisted of 18 students. The analysis of the data was conducted by following steps. Analyzing the quantitative data by using the rubric on assessing the students‟ writing from Brown namely content, organization, grammar, vocabulary and mechanics and analyzing the qualitative data through transcripts of structure interviews. After analyzing the data, it showed that the students‟ ability in writing descriptive text by using picture achieved the Good level. As the result, the research findings also indicate that the major contributions of the picture in writing descriptive text namely : the picture can be the real and exact image to help them write a descriptive text, the picture give some direction to the students to write, and using picture can make them more interested and motivated to write